Some aspects of the ethanol stability of red deer milk (Cervus elaphus hispanicus): A comparison with other dairy species. (November 2018) - de la Vara, Juan Angel; Berruga, María Isabel; Cappelli, Jamil; Landete-Castillejos, Tomás; Carmona, Manuel; Gallego, Laureano; Molina, Ana
Abstract: The ethanol stability, a freshness and heat stability indicator, of Iberian red deer milk was determined. Additionally, the interspecific differences in composition, physical, hygienic and technological parameters, in bulk tank milk obtained from red deer, sheep, goats and cows were compared. Red deer milk ethanol stability was similar to that of sheep milk; bovine milk was the most stable and goat milk the least. Ethanol stability was influenced by pH; within the range studied, increased pH increased stability, this effect being more noticeable in bovine milk than in milk from the other species. Milk composition presented evident differences among species, as did somatic cell counts, total bacterial count, pH and titratable acidity or density. The results suggest that milk of red deer is very similar to that of sheep, but is even richer in fat and proteins, making it an interesting and novel product with high potential in dairy industry.